Superiority trial of intermittent treatment with dihydroartemisinin-piperaquine versus sulfadoxine-pyrimethamine for the prevention of malaria during pregnancy - Roland Nnaemeka Okoro; Ado Danazumi Geidam; Audu Abdullahi Bukar; Abba Bukar Zarami; John David Ohieku; Alhaji Bukar Musa; Timothy Samuel Yerima (SpringerOpen, 2023)
Abstract Background Malaria in pregnancy is responsible for various adverse maternal and birth outcomes. The emerging resistance to sulfadoxine-pyrimethamine (SP) raises important concerns about its use for intermittent preventive treatment in pregnancy (IPTp) in Africa. This trial aimed to assess the efficacy and safety of IPTp with dihydroartemisinin-piperaquine (DP) as an alternative to IPTp with SP. Results The double-blind, randomized, and controlled superiority trial was conducted between July 2020 and June 2021. A total of 250 women were enrolled and randomly assigned to receive SP (n = 125) or DP (n = 125). Two hundred and six (82.4%) participants that contributed to the outcomes were included in the modified intention-to-treat (ITT) analysis, while 84 participants that completed the three courses of the study drugs were included in the per protocol (PP) analysis. The ITT analysis results showed that the incidence of histopathologically confirmed placental malaria was nonsignificantly higher in the DP group compared with the SP group (62.5% vs. 51.1%, P = 0.098). After adjusting for confounders, the risk of histopathologically confirmed placental malaria was also nonsignificantly higher in the DP group (Adjusted Relative Risk [RR] = 1.27, 95% CI 0.94-1.71) compared with the SP group. In contrast, the risk of a low APGAR score was significantly lower in the DP group (RR = 0.45, 95% CI 0.38-0.52) compared with the SP group. Also, the risk of a composite adverse birth outcome (low birth weight or preterm delivery or neonates small for the gestational age) was nonsignificantly lower in the DP group (Adjusted RR = 0.82, 95% CI 0.55-1.21) compared with the SP group. Both drugs were well tolerated, although nausea and vomiting occurred in a significant number of participants in the SP group. Conclusions A three-course IPTp with DP was safe and was not found to be superior to IPTp with SP in the prevention of placental malaria. Although IPTp with DP was associated with a significant lower risk of low APGAR score and nonsignificant lower risks of other adverse birth outcomes compared with IPTp with SP. Trial registration PACTR, PACTR202002644579177. Registered 20 February 2020, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=9753 .